2019
DOI: 10.1111/modl.12546
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates Chinese University Students to Learn Japanese? Understanding Their Motivation in Terms of ‘Posture’

Abstract: In light of popular nationalism on the rise in China and Japan, this inquiry develops and validates a survey instrument to document university students’ motivation to learn Japanese in mainland China and explore how the learning of a foreign language may lead to better cross‐cultural understanding. A total number of 398 Chinese learners of Japanese in Chinese universities participated in the survey and 12 of them participated further in post‐survey interviews. The results confirm that participants’ interest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
1
14
1
Order By: Relevance
“…In a study by Islam et al (2013), it was found that students with international posture showed relatively strong motivation. Similarly, this kind of posture was found in a study by Teo et al (2019).…”
Section: Criterion Measure and Other Possible Predictorssupporting
confidence: 81%
“…In a study by Islam et al (2013), it was found that students with international posture showed relatively strong motivation. Similarly, this kind of posture was found in a study by Teo et al (2019).…”
Section: Criterion Measure and Other Possible Predictorssupporting
confidence: 81%
“…Among the studies in the field of SLA, only a small amount of research has investigated language learning from the leisure perspective, with the consequence that LOTE learning is even more under-examined from this viewpoint. Previous studies of LOTE learning motivation [36] demonstrate the relationship between learners' cultural interests and language learning. Even for students learning LOTEs as majors, the LOTE ideal self seems to be related to travel plans, not to career plans [35].…”
Section: Language Learning As Leisure and Consumptionmentioning
confidence: 98%
“…It has been shown that in a LOTE context, immediate language‐learning experience becomes more significant in shaping learners’ motivational selves (Busse & Walter, 2013; de Burgh–Hirabe, 2019; Huang, 2019). At a macrosociological level, the motivational self‐images constructed by learners of LOTEs are also forcefully mediated by social discourse about multilingual learning (Lanvers, 2017; Lanvers et al., 2018), socioeconomic background (Coffey, 2018; Lanvers, 2018), international relations between the learner's home country and the target‐language community (Teo et al., 2019), and length of residence in the target‐language community (Oakes & Howard, 2019). To accommodate the contextual dimension, researchers have suggested revised conceptualizations of the L2 motivational self by reinstating the own–other dimension entailed in Higgins's (1987) original self‐discrepancy model (e.g., Lanvers, 2016, 2017; Thompson, 2017a; Thompson & Liu, 2018; Thompson & Vásquez, 2015).…”
Section: Theoretical Developments Of L2 Motivationmentioning
confidence: 99%